Point‐of‐Care Ultrasound Predicts Clinical Outcomes in Patients With COVID‐19. (1st September 2021) - Kumar, Andre; Weng, Isabel; Graglia, Sally; Lew, Thomas; Gandhi, Kavita; Lalani, Farhan; Chia, David; Duanmu, Youyou; Jensen, Trevor; Lobo, Viveta; Nahn, Jeffrey; Iverson, Nicholas; et al.
Abstract : Objectives: Point‐of‐care ultrasound (POCUS) detects the pulmonary manifestations of COVID‐19 and may predict patient outcomes. Methods: We conducted a prospective cohort study at four hospitals from March 2020 to January 2021 to evaluate lung POCUS and clinical outcomes of COVID‐19. Inclusion criteria included adult patients hospitalized for COVID‐19 who received lung POCUS with a 12‐zone protocol. Each image was interpreted by two reviewers blinded to clinical outcomes. Our primary outcome was the need for intensive care unit (ICU) admission versus no ICU admission. Secondary outcomes included intubation and supplemental oxygen usage. Results: N = 160 patients were included. Among critically ill patients, B‐lines (94 vs 76%; P < .01) and consolidations (70 vs 46%; P < .01) were more common. For scans collected within 24 hours of admission (N = 101 patients), early B‐lines (odds ratio [OR] 4.41 [95% confidence interval, CI: 1.71–14.30]; P < .01) or consolidations (OR 2.49 [95% CI: 1.35–4.86]; P < .01) were predictive of ICU admission. Early consolidations were associated with oxygen usage after discharge (OR 2.16 [95% CI: 1.01–4.70]; P = .047). Patients with a normal scan within 24 hours of admission were less likely to require ICU admission (OR 0.28 [95% CI: 0.09–0.75]; P < .01) or supplemental oxygen (OR 0.26 [95% CI: 0.11–0.61]; P < .01). Ultrasound findings did not dynamically change over a 28‐day scanning window after symptom onset. Conclusions: Lung POCUS findings detected within 24 hours of admission may provide expedient risk stratification for important COVID‐19 clinical outcomes, including future ICU admission or need for supplemental oxygen. Conversely, a normal scan within 24 hours of admission appears protective. POCUS findings appeared stable over a 28‐day scanning window, suggesting that these findings, regardless of their timing, may have clinical implications.